Physical exercise, IGF-1 and cognition: A systematic review of experimental studies in the elderly - Stein, Angelica Miki [UNESP]; Silva, Thays Martins Vital [UNESP]; Coelho, Flávia Gomes de Melo [UNESP]; Arantes, Franciel José [UNESP]; Costa, José Luiz Riani [UNESP]; Teodoro, Elizabeth; Santos-Galduróz, Ruth Ferreira (FapUNIFESP (SciELO), 2018)
One of hypothetical mechanisms related to cognition is exercise-induced IGF-1. Objective: The aim of this study was to analyze the effects of exercise on IGF-1 levels and cognition in the elderly. Methods: The article searches were conducted on Pubmed, Web of Science, PsycINFO and Scielo databases and reviewed according to PRISMA guidelines. The inclusion criteria were: [1] original articles published up to 2017; [2] samples including elderly; [3] protocols including physical exercise; [4] longitudinal studies having exercise as main outcome; [5] assessment of IGF-1; [6] cognition assessment. Results: Seven studies were included in this review. Three of the studies showed an exercise-induced increase in IGF-1; three found stable IGF-1 levels and one found a reduction in IGF-1; with and without improvement in cognition. Conclusion: Disparities in the type of physical exercise, protocols and samples under different conditions hinder the establishment of a consensus on IGF-1, cognition and physical exercise.
Exercício físico, IGF-1 e cognição: Uma revisão sistemática de estudos experimentais em idosos
Keywords: Cognition; Exercise; Older adults